Looking for influence of the chromosome number, ploidy level and nuclear 2C value on the in vitro response in Passiflora genus - Leite, Cristiana Torres (2016)
As well as for other taxa, different morphogenetic in vitro responses (direct/indirect organogenesis or embryogenesis) have been reported for the Passiflora species, even in the same in vitro environmental conditions. The distinct chromosome number between some Passiflora genus species has been appointed as a possible genetic factor related to the differences in in vitro responses. Based on this hypothesis, this study aimed to evaluate the in vitro responses of Passiflora species exhibiting distinct chromosome number, ploidy level and nuclear DNA content to answer the following questions: these genomic aspects influence the in vitro response? For this, mature zygotic embryos (MZE) of five species, which belong the four Passiflora subgenus, were inoculated in MS medium supplemented with 4.4 µM de benzylaminopurine (BAP) and nine concentrations of 2,4-dichlorophenoxyacetic acid (4.53 – 144.96 µM 2,4-D). Corroborating to the previous studies, different morphogenic responses were observed under the same in vitro conditions. Only friable calli (FC) were obtained from MZE of Passiflora coriacea Juss (2n = 12 chromosomes, 2C = 1.00 pg), Passiflora lindeniana TR & Planch (2n = 24, 2C = 2.42 pg) and Passiflora contracta Vitta (2n = 48 chromosomes, 2C = 4.78 pg). Plantlets were recovered from MZE of Passiflora foetida L. (2n = 20, 2C = 1.04 pg) and Passiflora miniata Vanderpl. (2n = 18, 2C = 3.40 pg) from indirect organogenesis and embryogenesis, respectively. As in other studies, plantlets were regenerated from indirect somatic embryogenesis only for the Passiflora species with 2n = 18 chromosomes (P. miniata). In spite of the chromosome number and ploidy level relatively lower than other Passiflora taxa, the nuclear genome size of the species with 2n = 18 is relatively higher. So, the karyotype changes (polyploidy, hybridization and disploidy) that wide occur during evolution in Passiflora probably resulted in distinct copy number of the genes related to plant morphogenic process. Therefore, for Passiflora genus is important to simultaneously look some genomic characteristics to understand the in vitro responses.